TOWARD ZERO-CARBON SHIPPING IN MALAYSIA: A COMPARATIVE ANALYSIS OF WTT AND TTW EMISSIONS - MHD RUSLAN, SITI MARSILA; MOKHTAR, KASYPI; WAN MANSOR, WAN NURDIYANA; ABU BAKAR, ANUAR (Journal of Maritime Logistics, 2025)
The maritime sector in Malaysia is at a critical juncture in its pursuit of zero-carbon shipping, which requires a strategic shift toward cleaner fuel alternatives. This study conducts a comparative analysis of Well-to-Tank (WTT) and Tank-to-Wake (TTW) emissions for six alternative marine fuels namely liquefied natural gas (LNG), methanol, biofuels, green ammonia, hydrogen and shore power. Drawing on internationally recognised emission factors and contextualised with Malaysia’s energy profile, the analysis reveals significant variations in emissions distribution across fuel types. Fuels such as green ammonia, hydrogen, and shore power exhibit zero TTW emissions, positioning them as long-term solutions, while biofuels offer a viable transitional pathway with a balanced emissions profile. Conversely, LNG and fossil methanol remain TTW-dominant and offer limited GHG reduction. The study presents a policy-oriented fuel selection framework, emphasising the importance of aligning fuel strategies with national decarbonisation goals, grid decarbonisation progress, and infrastructure readiness. The findings aim to support Malaysia’s transition towards a sustainable and climate-resilient maritime sector.